Development of non-phytotoxic concentration of nemarioc-al and nemafria-bk on beetroot (beta vulgaria) ciltivar 'detroit dark red' - Mashitoa, Mamakgana Florence (My University, 2017)
Phytonematicides, mainly due to their allelopathic nature, might be highly phytotoxic to crops protected against nematode damage. Phytotoxicity issues are compounded by the fact that the efficacy of plant extracts on nematode suppression depended much on their concentration and duration of exposure to the nematodes. Phytotoxicity could result in low crop yield and/or even in the eventual death of the protected crops. Concentrations that were suppressive to nematode numbers, but phytotoxic to the tested crop would not be useful when applied as a post-planting phytonematicides. The Mean Concentration Stimulation Point (MCSP) values were developed from the Curve fitting Allelochemical Response Dosage (CARD)computer based model to ensure that a non-phytotoxic concentration was applied for each crop. The objective of this study was to determine whether a series of Nemarioc-AL and Nemafric-BL phytonematicide concentrations would provide the MCSP for beetroot (Beta vulgaris) under greenhouse, microplot and field conditions. The greenhouse treatments included 0, 2, 4, 8, 16 and 32% for each phytonematicide. The microplot treatments were 0, 0.8, 1.6, 3.2, 6.4 and 12.8% concentrations, whereas in the field trial treatments were 0, 2.4, 4.8, 9.6, 19.2 and 38.4%. Under each condition, treatments of Nemarioc-AL and Nemafric-BL phytonematicides were, in separate experiments arranged in a randomised complete block design, with the greenhouse, microplot and field trials having 15, 10 and 9 replications, respectively. In the greenhouse, seedlings were raised in 20cm diameter plastic pots, containing pasteurised river sand and commercial seedling growing medium Hygromix® at 3:1 (v/v) ratio. Each seeding was inoculated with 5000 eggs and second-stage juveniles (J2) of Meloidogyne incognita. Seedlings were irrigated with chlorine free tapwater every other day using 250 ml/plant, with irrigation substituted by the treatment once weekly. On the microplot, the procedures were as in the greenhouse except that they growing mixture comprised pasteurised soil collected from the site. In the field, seedlings were directly transplanted into the soil. At 56 days after inoculation, in the greenhouse trial, the effects of Nemarioc-AL and Nemafric-BL phytonematicides were highly significant (P ≤ 0.01) on root galls, contributing 77 and 72% in total treatment variation (TTV) of root galls, respectively. Relative to untreated control, the respective products reduced root galls by 28-72% and 43-67%. Nemarioc-AL and Nemafric-BL phytonematicides had MCSP values on beetroot of 18.1 and 6.4%, respectively, with overall sensitivity values of 0 and 1, respectively.There was no treatment effect on nematode since there was absence of nematode in untreated control.Under microplottrials,Nemafric-BL phytonematicide had significant (P≤ 0.05) effects on fresh root mass, dry root mass and root galls, contributing 20, 19 and 57% in TTV of the three variables, with relative increases for fresh root mass and dry root mass of 65-159% and 63-143%, respectively, whereas root galls were reduced by 82-100%. Nemafric-BL phytonematicide had MCSP value on beetroot of 10.2%, with overall sensitivity value of 4 units. There was no treatment effect on nematode since there was absence of nematode in untreated control. In microplots, Nemarioc-AL phytonematicide did not have significant effects on all plant variables. Under field conditions, the treatments did not have significant effects on plant variables. In conclusion, results of the current study suggested that under greenhouse and microplot conditions the MCSP values of the phytonematicides ranged from 6.4 to 18.1%, with a wide range of overall sensitivities of phytonematicides to the test of beetroot cultivar
Thesis (M.Sc. Agriculture (Horticulture)) -- University of Limpopo, 2017
Keywords: Phytonematicides; Phytotoxicity; Crop yield; Nematode; Plants nematodes; Root-knot nematodes; Beets